COOPERATION WITH BUSINESS AS AN EXPRESSION OF THE IMPLEMENTATION OF THE ENTREPRENEURIAL UNIVERSITY MODEL. A CASE STUDY - Bukowska-Piestrzyńska, Agnieszka (Management and Administration Journal, 2024)
Since the innovativeness of the economy is influenced by education and science (especially higher education), building bridges between the worlds of science and business has become a necessity. This approach is reflected in the practical implementation of the entrepreneurial university model. This article presents the essence of this model, with particular emphasis on the university-business cooperation along with the resulting benefits and selected areas of its implementation. The aim of the article is to indicate the activities of universities that fit into the entrepreneurial univer-sity model. Versatile forms of cooperation with enterprises implemented in 2017-2023 were indicated on the example of the activity of the Department of Logistics and Innovations of the University of Łódź. The study used the participant observation method. The article is of a theoretical and empirical nature.